Modernisasi Aspek Relasional Pemerintah Daerah: Menengok Sejarah, Menatap Masa Depan - Samodra Wibawa (Magister Administrasi Publik, 2000)
The history of Nusantara was since 1600s broken down by the Europeans, so that it has developed not in a